Ã¦Â§â€¹Ã©â‚¬Â Ã¨Â¨â‚¬Ã¨ÂªÅ¾Ã¥ÂÂ¦Ã£ÂÂ«Ã§Ââ€ Ã¨Â«â€“Ã§Å¡â€žÃ¥Å¸ÂºÃ§â€ºÂ¤Ã£â€šâ€™Ã§Â½Â®Ã£ÂÂÃ¦â€”Â¥Ã¦Å“Â¬Ã¨ÂªÅ¾Ã¦â€¢â„¢Ã¨â€šÂ² (JAPANESE LANGUAGE EDUCATION BASED ON THE THEORY OF STRUCTURAL LINGUISTICS) - Setiawati, Ai Sumirah (Language Circle: Journal of Language and Literature, 2010)
Structural Linguistics is an approach to linguistics originating from the work of Swiss Linguist Ferdinand de Saussure. Saussure stressed examining language as a static system of interconnected units. Structural Linguistics involves collecting a corpus of utterances and then applying discovery procedures to them in an attempt to classify all of the elements of the corpus at their different linguistic levels as the phonemes, morphemes, word classes, noun phrases, verb phrases, and sentence types. After Saussure, the history of Structural Linguistics branches off in two separate directions. First, in America, linguist Leonard Bloomfield's reading of Saussure's course proved influential, bringing about the Bloomfieldean phase of phase in American Linguistics that lasted from the mid 1930s to the mid 1950s. Second, in Europe, Saussure influenced the Prague School of Roman Jakobson and Nikolai Trubetzkoy, whose work would prove hugely influential, particularly concerning phonology, and the Copenhagen School of Louis Hjelmslev. Teaching methods which are based on structral linguistics are ASTP (Army Specialized Training Program) and Audio Lingual Method (AL-Method) also known as Michigan Method, Fries Method, or Oral Approach. During World War II (1943-1044), there were 20 countries which used these teaching methods including Japan, and brought a great result especially in Japanese language education. Keywords: Structural Linguistics, Saussure, ASTP, Audio Lingual Method, Japanese Language Education